On mennicke groups of deficiency zero I - Muhammad A. Albar (International Journal of Mathematics and Mathematical Sciences)
The Mennicke group M(m,n,r)=〈x,y,z,|xy=xm, yz=yn, zx=zr〉 is one of the few known 3-generator groups of deficiency zero. Several cases of M(m,n,r) are studied.